THE EFFECT OF TRAINING AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE MEDIATED BY COMPETENCY AT THE CENTER MEDAN PALM OIL RESEARCH - Dini Hendriani; Bunga Aditi; Ilham Mubaraq Ritonga (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the effect of training and work discipline on employee performance with competence as a mediating variable at the Medan Palm Oil Research Center. The research method uses a quantitative approach with Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis techniques. The study population was 235 employees with a sample of 100 respondents determined using the Slovin formula. Data were collected through a questionnaire with a Likert scale and analyzed using SmartPLS version 3. The results showed that training had a significant positive effect on employee performance (β = 0.419; p = 0.001) and competence (β = 0.354; p = 0.000). Work discipline had a significant positive effect on employee performance (β = 0.551; p = 0.000) and competence (β = 0.147; p = 0.001). Competence had a significant positive effect on employee performance (β = 0.005; p = 0.000). Mediation testing demonstrated that competence mediated the effect of training on employee performance (p=0.002) and work discipline on employee performance (p=0.002). This study emphasizes the importance of developing continuous training and strengthening a culture of discipline to improve employee competence and performance.